The CARMA-NRO orion survey: filamentary structure as seen in C18O emission - Suri, Sümeyye; Klessen, Ralf S. (Astronomy and astrophysics, 2019)
Context: We present an initial overview of the filamentary structure in the Orion A molecular cloud utilizing a high angular and velocity resolution C18O(1-0) emission map that was recently produced as part of the CARMA-NRO Orion Survey. Aims: The main goal of this study is to build a credible method to study varying widths of filaments which has previously been linked to star formation in molecular clouds. Due to the diverse star forming activities taking place throughout its ~20 pc length, together with its proximity of 388 pc, the Orion A molecular cloud provides an excellent laboratory for such an experiment to be carried out with high resolution and high sensitivity. Methods: Using the widely-known structure identification algorithm, DisPerSE, on a three-dimensional (PPV) C18O cube, we identify 625 relatively short (the longest being 1.74 pc) filaments over the entire cloud. We studied the distribution of filament widths using FilChaP, a python package that we have developed and made publicly available. Results: We find that the filaments identified in a two square-degree PPV cube do not overlap spatially, except for the complex OMC-4 region that shows distinct velocity components along the line of sight. The filament widths vary between 0.02 and 0.3 pc depending on the amount of substructure that a filament possesses. The more substructure a filament has, the larger is its width. We also find that despite this variation, the filament width shows no anticorrelation with the central column density which is in agreement with previous Herschel observations.
Die Zahl „18“ ist im Zusatz zum Titel hochgestellt
Gesehen am 24.05.2019